ON THE RELATION BETWEEN LINGUISTIC AND ENCYCLOPEDIC INFORMATION IN THE «EXPLANATORY DICTIONARY OF THE RUSSIAN LANGUAGE» EDITED BY D. N. USHAKOV - Gozel O. Ilagaeva (Вестник Северо-Кавказского федерального университета)
The article investigates the synthesis of linguistic and encyclopedic information. This principle is illustrated by the example of "ExplanatoryDictionary of the Russian Language" edited by D.N.Ushakov. The basic ways of expressing linguistic and encyclopedic informationin the dictionary by D.N.Ushakov are illustrated. The article emphasizes the importance of such dictionaries for the development of such areas of linguistics as cultural linguistics, philosophy and sociology of language, linguistic geography, linguistic biology, etc.